2014
DOI: 10.3109/10826084.2014.913630
|View full text |Cite
|
Sign up to set email alerts
|

Indicators of Club Management Practices and Biological Measurements of Patrons’ Drug and Alcohol Use

Abstract: Background Electronic Music Dance Events in nightclubs attract patrons with heavy alcohol/drug use. Public health concerns are raised from risks related to these behaviors. Practices associated with increased risk in these club settings need to be identified. Objectives The relationship between club management practices and biological measures of patrons’ alcohol/drug use is examined. Methods Observational data from 25 events across 6 urban clubs were integrated with survey data (N=738 patrons, 42.8% femal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 32 publications
1
9
0
Order By: Relevance
“…A total of 1,714 participants provided sufficient information (out of 2,099 who provided any data) to be included in this study. Club and event selection procedures and the methodologies are described more fully in Miller et al (2013), Byrnes et al (2014), and Voas et al (2006).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 1,714 participants provided sufficient information (out of 2,099 who provided any data) to be included in this study. Club and event selection procedures and the methodologies are described more fully in Miller et al (2013), Byrnes et al (2014), and Voas et al (2006).…”
Section: Methodsmentioning
confidence: 99%
“…Over the past decade, the research team has conducted surveys with young adults attending clubs that sponsor electronic music dance events (EMDEs) (Byrnes, Miller, Johnson, & Voas, 2014; Miller, Byrnes, Branner, Voas, & Johnson, 2013; Miller et al, 2009; Miller, Furr-Holden, Voas, & Bright, 2005). Using the portal survey method (Voas et al, 2006), in which information is collected from clients on entry and exit from drinking environments (e.g., nightclubs), it is possible to study attendees’ perceptions of safety as a function of observed staff and security practices, as well as their attitudes toward returning to that same club.…”
Section: Introductionmentioning
confidence: 99%
“…In considering the nested nature of potential risk, we situated our thinking in a social-ecological approach (Gruenewald, 2007) to on-premise drinking locations, an approach which considers ways in which consumption is influenced by social factors such as: Topology State, city, and local ordinances have a differential impact on both alcohol consumption and aggression (Bellis et al, 2008; Giancola, 2002) which can mediate the effect of drinking establishments on the larger environment Context Management policies and staffing practices within a given club, such as a permissive attitude toward alcohol consumption, drink promotions, and staff demographics (Byrnes, Miller, Johnson, & Voas, 2014; Clapp, 2010; Graham & Homel, 2008; Green & Plant, 2007; Homel, Carvolth, Hauritz, McIlwain, & Teague, 2004; Ker & Chinnock, 2008; Macintyre & Homel, 1997; Roberts, 2009) can contribute to safety within the club Agency Individual patrons’ social backgrounds, such as age and gender (Harford, Wechsler, & Muthen, 2003), or sexual orientation (Miller et al, 2015), have influence how much they drink (Graham, Osgood, Wells, & Stockwell, 2006) which in turn can contribute to involvement in aggression Contacts Hosted event and patron characteristics result in potentially different interactions across and within social groups that impact risk behaviours. Intra-group influences can directly impact on alcohol consumption, with some drinking groups tending to consume too much alcohol (Larimer, Turner, Mallett, & Geisner, 2004; Neighbors, Lindgren, Knee, Fossos, & DiBello, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Context Management policies and staffing practices within a given club, such as a permissive attitude toward alcohol consumption, drink promotions, and staff demographics (Byrnes, Miller, Johnson, & Voas, 2014; Clapp, 2010; Graham & Homel, 2008; Green & Plant, 2007; Homel, Carvolth, Hauritz, McIlwain, & Teague, 2004; Ker & Chinnock, 2008; Macintyre & Homel, 1997; Roberts, 2009) can contribute to safety within the club…”
Section: Introductionmentioning
confidence: 99%
“…The electronic dance music (EDM) nightclub scene is found in almost every large city, but is especially prevalent in major tourist destinations, including Miami, where people tend to look for an escape from their routines (Owen, 2003; Shister, 1999; Uriely & Belhassen, 2006). Ecstasy is a popular drug in the EDM nightclub scene, but use of other “club drugs” (e.g., powder cocaine, methamphetamine, ketamine, rohypnol, gamma-hydroxybutyric acid [GHB], lysergic acid diethylamide [LSD], and marijuana) is also prevalent and has tended to vary over time and location (Byrnes, Miller, Johnson, & Voas, 2014; Kelly, LeClair, & Parsons, 2013; Measham, Aldridge, & Parker, 2001; Miller, Byrnes, Branner, Voas, & Johnson, 2013; Reynolds, 1998; Sanders, 2006; Shacham & Cottler, 2010). The nonmedical use of prescription medications has also become popular in the EDM nightclub scene—most typically benzodiazepines and opioid analgesics (Buttram & Kurtz, 2016; Kelly & Parsons, 2007; Kurtz, Buttram, & Surratt, 2016; Kurtz, Inciardi, Surratt, & Cottler, 2005; Kurtz, Surratt, Buttram, Levi-Minzi, & Chen, 2013).…”
Section: Introductionmentioning
confidence: 99%